Stimulated Platelet Aggregation, Thromboxane B2 Formation and Platelet Sensitivity to Prostacyclin - A Critical Evaluation - Siess, Wolfgang; Roth, Peter; Weber, Peter C (Thrombosis and Haemostasis, 1981)
Platelets have been implicated in the development of atherosclerotic and thrombotic vascular diseases. Evaluation of platelet aggregation in relation to endogenously formed compounds which affect platelet function may provide information of clinical and pharmacological relevance. We describe a method in which thromboxane B2 (TXB2) formation was analyzed following stimulation of platelet-rich plasma (PRP) with ADP, 1-epinephrine, collagen, and arachidonic acid. In addition, we determined platelet sensitivity to prostacyclin following ADP- and collagen-induced platelet aggregation. The parameters under study were found to depend on the platelet count in PRP, on the type and dose of the aggregating agent used, and on the test time after blood sampling. By standardization of these variables, a reliable method was established which can be used in clinical and pharmacological trials.
Keywords: Platelet aggregation; Thromboxane B2 formation; Aggregating agents; Prostacyclin-sensitivity